PENGARUH STORE ATMOSPHERE SERVICE QUALITY TERHADAP KEPUTUSAN PEMBELIAN MEMBERSHIP DI PRESTIGE FITNES MALANG: Manajemen Pemasaran - Cinthia, Resti; Samboro , Joko (Musytari : Jurnal Manajemen, Akuntansi, dan Ekonomi, 2025)
Store Atmosphere and Service Quality influence consumer purchasing decisions. Store atmosphere is a consideration when purchasing a product or service, but good service quality is also crucial for creating special treatment for customers. Observations indicate that Prestige Fitness Malang has not provided excellent service, as evidenced by the fluctuation in the number of active and new members. This study aims to analyze service quality at Prestige Fitness Malang and the impact of store atmosphere and service quality on customer satisfaction. This explanatory study examines the relationship between the independent variables of store atmosphere and service quality and the dependent variable of purchasing decisions. Data were collected through observation and questionnaires using purposive sampling techniques, involving 100 Prestige Fitness Malang member respondents, and analyzed using multiple regression. The calculated t-value of Store Atmosphere was 6.803 > t-table 1.661, with a significance level of 0.000 < 0.05, indicating that this variable has a partial impact on purchasing decisions. The calculated t-value for Service Quality of 5.079 > t-table 1.661 with a significance level of 0.000 < 0.05 indicates that this variable also has a significant partial impact on Purchasing Decisions. Furthermore, the calculated F-value of 35.883 > F-table 3.09 with a significance level of 0.000 < 0.05 indicates that Store Atmosphere and Service Quality simultaneously have a significant influence on Purchasing Decisions. The results of this study indicate that Prestige Fitness Malang needs to maintain member engagement by providing a quality gym experience and a clean and healthy atmosphere to increase their desire to remain members.